Construction of tetrahydrobenzo[f]quinoline scaffolds via polar [4 + 2]-Cycloaddition reaction with arynes as dienophiles. (6th July 2022) - Pandya, Virat G.; Mhaske, Santosh B.
Graphical abstract: Abstract: A transition-metal-free route has been developed for the direct synthesis of biologically significant tetrahydrobenzo[ f ]quinoline scaffolds. The reaction features polar [4 + 2] Diels-Alder cycloaddition reaction of arynes with a well-designed diene N -Boc protected vinyl tetrahydropyridine, followed by the isomerisation of the double bond leading to the formation of tetrahydrobenzo[ f ]quinoline scaffolds in good to moderate yields.